A study on the photocatalytic degradation performance of a [KNbO3]0.9-[BaNi0.5Nb0.5O3−δ]0.1 perovskite. Issue 3 (8th January 2020) - Zhang, Duoying; Lv, Shan; Luo, Zhi
Abstract : In this study, [KNbO3 ]0.9 -[BaNi0.5 Nb0.5 O3− δ ]0.1 (KBNNO) perovskite powder was synthesized via a conventional solid-phase reaction method. Abstract : In this study, [KNbO3 ]0.9 -[BaNi0.5 Nb0.5 O3− δ ]0.1 (KBNNO) perovskite powder was synthesized via a conventional solid-phase reaction method. The crystal structure of the KBNNO powder was characterized on an X-ray diffractometer. The size and surface morphology of the particles were investigated via field emission electron scanning microscopy (FE-SEM). The KBNNO powder particles were stacked from a smooth flat layer. The photocatalytic activity of KBNNO was investigated using a methylene blue (MB) aqueous solution as a model organic substrate. The results showed that the KBNNO powder has excellent photocatalytic degradation performance. The effects of catalyst loading and the initial concentration of the MB solution on the photocatalytic activity were also investigated in this study. The experimental results proved that both catalyst loading and the initial dye concentration are important factors affecting photocatalytic degradation. As the catalyst loading increases, the photocatalytic activity increases. However, the growth rate of the degradation efficiency gradually decreases. Also, the degradation efficiency gradually decreased with the initial concentration of MB.